3-D structured porous carbons with virtually any shape from whey powders. (30th April 2021) - Llamas-Unzueta, Raúl; Menéndez, J. Angel; Ramírez-Montoya, Luis A.; Viña, Jaime; Argüelles, Antonio; Montes-Morán, Miguel A.
Abstract: The conventional carbonisation (450-1000 °C) of whey powders gives totally unexpected results in terms of the mechanical integrity of the resulting carbons. Pieces of different geometries can be easily prepared by pouring the powders loosely into a mould. This green precursor adopts the shape of the predesigned mould at relatively low temperatures (120-150 °C) through the sintering of the whey particles surfaces. The shape of the pre-conformed pieces is preserved at least up to 1000 °C under N2 atmosphere, with a linear shrinkage of ca. 23%. The flexural strength and modulus of the resulting 3-D structured porous carbons are outstanding for a biomass derived carbon monolith, and their abrasiveness exceptionally low, similar to porous monoliths derived from phenolic resins. In addition, carbons obtained at temperatures above 800 °C develop a hierarchical porosity covering from micropores to macropores up to 400 μm granting high permeable structures. It is postulated that the presence of both lactose and whey proteins in whey powders is key for their atypical behaviour during carbonisation. Graphical abstract: Image 1 Highlights: Atmospheric pressure casting of whey powder and subsequent carbonization produces very consistent porous carbon structures. The mechanical properties of the 3D whey carbons are similar to those of porous carbon monoliths derived from resins. Powdered whey does not melt when heated, but sinters at 150 ° C. Whey powder carbonization differs strongly from the pyrolysis behavior of its main components, lactose and whey proteins.